Indices to evaluate the performance of force transmission and constraint for parallel mechanisms - Zhang, Tie (Strojniški vestnik, 2022)
The force transmission and constraint ability significantly influence the performance of parallel mechanisms (PMs), such as force dexterity, overall rigidity and accuracy. The transmission wrench screw (TWS) transmits the force between the actuator and end-effector, and the constraint wrench screw (CWS) resists structural deformations. They significantly influence the manipulability to transmit force and the consistency to resist deformations. In this study, two new indices are proposed to evaluate their manipulability and consistency. The indices are notable for their unit homogeneity, frame independence, and measurement facility without interference. By taking three PMs with different mobility properties as examples, the effectiveness of the two indices for evaluating the manipulability to transmit force and the consistency to resist deformations is verified. Based on the indices, the configuration of a 3-CRU (C a cylindrical joint, R a revolute joint, and U a universal joint) PM with optimal force transmission and constraint ability is constructed.
Keywords: force constraint consistency; force transmission; omejevanje sil; paralelni mehanizmi; parallel mechanism; prenos sile; screws; vijaki